Group psychodrama and chemical dependency: working professional projects and leisure experiences - Gambin, Katiussa Aparecida (2020)
The present study aimed to identify how group psychodrama helps in the construction of professional projects for drug addicts and how it contributes to addicts to experience leisure activities. A qualitative study was carried out in an action research format. In total, 7 group psychodrama sessions were held, with 6 users of a Psychosocial Care Center II Alcohol and Other Drugs, however, the research carried out an analysis section of two sessions, which focused on the theme of work and leisure. The analysis was guided by the theoretical and epistemological precepts of Psychodrama and the literature on chemical dependency. With regard to work, there was a difficulty in managing the salary and the need for participants to assume an autonomous posture in the search for professional projects. Group psychodrama was also identified as a tool for rescuing innate resources for understanding and overcoming cultural preserves that limited leisure experiences. It should be noted that the financial issue also arises as an impediment to leisure, articulated with the difficulty of entering or staying in the occupational environment.